Cholinergic and Neuroimmune Signaling Interact to Impact Adult Hippocampal Neurogenesis and Alcohol Pathology Across Development - Macht, Victoria A.; Vetreno, Ryan P.; Crews, Fulton T. (Frontiers in Pharmacology, 2022)
Alcohol (ethanol) use and misuse is a costly societal issue that can affect an individual across the lifespan. Alcohol use and misuse typically initiates during adolescence and generally continues into adulthood. Not only is alcohol the most widely abused drug by adolescents, but it is also one of the most widely abused drugs in the world. In fact, high rates of maternal drinking make developmental ethanol exposure the most preventable cause of neurological deficits in the Western world. Preclinical studies have determined that one of the most consistent effects of ethanol is its disruption of hippocampal neurogenesis. However, the severity, persistence, and reversibility of ethanol’s effects on hippocampal neurogenesis are dependent on developmental stage of exposure and age at assessment. Complicating the neurodevelopmental effects of ethanol is the concurrent development and maturation of neuromodulatory systems which regulate neurogenesis, particularly the cholinergic system. Cholinergic signaling in the hippocampus directly regulates hippocampal neurogenesis through muscarinic and nicotinic receptor actions and indirectly regulates neurogenesis by providing anti-inflammatory regulatory control over the hippocampal environmental milieu. Therefore, this review aims to evaluate how shifting maturational patterns of the cholinergic system and its regulation of neuroimmune signaling impact ethanol’s effects on adult neurogenesis. For example, perinatal ethanol exposure decreases basal forebrain cholinergic neuron populations, resulting in long-term developmental disruptions to the hippocampus that persist into adulthood. Exaggerated neuroimmune responses and disruptions in adult hippocampal neurogenesis are evident after environmental, developmental, and pharmacological challenges, suggesting that perinatal ethanol exposure induces neurogenic deficits in adulthood that can be unmasked under conditions that strain neural and immune function. Similarly, adolescent ethanol exposure persistently decreases basal forebrain cholinergic neuron populations, increases hippocampal neuroimmune gene expression, and decreases hippocampal neurogenesis in adulthood. The effects of neither perinatal nor adolescent ethanol are mitigated by abstinence whereas adult ethanol exposure-induced reductions in hippocampal neurogenesis are restored following abstinence, suggesting that ethanol-induced alterations in neurogenesis and reversibility are dependent upon the developmental period. Thus, the focus of this review is an examination of how ethanol exposure across critical developmental periods disrupts maturation of cholinergic and neuroinflammatory systems to differentially affect hippocampal neurogenesis in adulthood.